Quality control methods of shortcuts biscuits using highly non-traditional raw materials - Kambulova, Yuliia; Kokhan, Olena; Zabroda, Artem (My University, 2023)
У статті представлено результати дослідження, спрямовані на збагачення рецептурного складу здобного печива шляхом заміни пшеничного борошна на борошно амарантове та суміш пророщених злакових з одночасним регулюванням його цукровмісту введенням полідекстрози. На основі проведених теоретичних і експериментальних досліджень встановлено, що максимально можливою є заміна 50 % пшеничного борошна на амарантове, яка не погіршує смак і аромат готової продукції, але надає як тісту, так і готовій продукції темних кольорів. Експериментально підтверджено можливість внесення полідекстрози на заміну 50 % цукрової пудри для покращення структурно-механічних характеристик тіста на основі суміші амарантового борошна, суміші пророщених злакових і пшеничного борошна, але вплив на пластичні характеристики такої заміни несуттєвий. Для досягнення необхідних показників якості запропоновано введення ферментного препарату целюлолітичної дії. У технологічну схему виробництва здобного пісочно-виїмного печива з високим вмістом нетрадиційної сировини запропоновано впровадити стадію відлежування тіста з підтриманням температури 35°С.

The article presents the results of a study aimed at enriching the recipe composition of shortbread cookies by replacing wheat flour with amaranth flour and a mixture of sprouted cereals with simultaneous regulation of its sugar content by introducing polydextrose. Based on conducted theoretical and experimental studies, it was found that the maximum possible is the replacement of 50% of wheat flour with amaranth, which does not worsen the taste and aroma of the finished product, but gives both the dough and the finished product dark colors. The possibility of introducing polydextrose to replace 50% of powdered sugar to improve the structural and mechanical characteristics of the dough based on a mixture of amaranth flour, a mixture of sprouted cereals and wheat flour has been experimentally confirmed, but the impact on the plastic characteristics of such a replacement is insignificant. To achieve the required quality indicators, the introduction of an enzyme preparation with cellulolytic action has been proposed. It is proposed to introduce a dough aging stage with a temperature of 35°C into the technological scheme for the production of buttery shortcrust cookies with a high content of non-traditional raw materials.
Keywords: печиво; борошно амарантове; полідекстроза; суміш пророщенних злакових; структура тіста; пластичність; ферментні препарати; кафедра технології хлібопекарських і кондитерських виробів; cookies; amaranth flour; polydextrose; dough structure; plasticity; enzyme preparations